PLAGIARISM IN SCIENTIFIC RESEARCH AND PUBLICATIONS - Yusupov Jasurbek Melsovich (American Journals, 2023)
Plagiarism, means of fighting against plagiarism, as well as its forms are investigated. Plagiarism refers to negative phenomena, both in all areas of human life, and in the scientific field. Unfortunately, at present, copyright infringement in the form of plagiarism in dissertations, articles, publications, etc. is increasingly common. This fact is mainly associated with the development of the Internet, various means of photocopying, as well as the impunity of plagiarists. Plagiarism, auto-plagiarism and compilation are inevitable consequences of the pursuit of the number of publications. They have their reasons and consequences, which are disclosed in the article. In the conditions of forced stamping by scientists of as many articles as possible, plagiarism has become an inevitable means of creating them for some authors, therefore, the article analyzes the history of its occurrence, clarifies its definition and consequences, presents ways to reduce its volume and combat it.
Keywords: plagiarism, compilation, auto-plagiarism, causes of ethical violations, consequences of plagiarism, protection of moral rights, copyright.